Gender and Precarious Research Careers : A Comparative Analysis. - Murgia, Annalisa. (Taylor & Francis Group, 2018)
Gender and Precarious Research Careers aims to advance the debate on the process of precarisation in higher education and its gendered effects, and springs from a three-year research project across institutions in seven European countries: Italy, Belgium, the Netherlands, Iceland, Switzerland, Slovenia and Austria.